The evolution and transformation of baju kurung in the peninsular of Malaysia / Asliza Aris - Aris, Asliza (2014)
Baju Kurung has existed over more than 600 years ago. It has been the pride and heritage of the Malay society since the Great Malaccan Sultanate in the IS*** Century. Since then, Baju Kurung has gone through some changes, which include its length, cut and shape, fabrics, style and coordination. Baju Kurung name is well- known to Malaysian society especially to the Malay people. It is common that any garment that resemblance the form of Baju Kurung is often called Baju Kurung (Moden). Due to this assumption, this research tends to construct an understanding that draws the line between traditional Baju Kurung and Baju Kurung Moden. Hence, the character definition of Baju Kurung is clearly drawn. The research looks at historical study of the Baju Kurung through references of historical literature, journals and visual evidence (photographic documentations) obtained from the libraries, museums, National Archive Malaysia and personal collections. A study of samples of man’s and woman’s Baju Kurung constructed a systematic analysis to document the Baju Kurung’s workmanship, measurement and fabric choice during a certain period of time. From historical study, literature review of current trend and the study of the Baju Kurung samples the research successfully trace the chronology of the development of Baju Kurung in the Peninsular of Malaysia. Unstructured interviews were conducted with people who were involved with Baju Kurung industries, academia, traditionalists and maker. The issues that incorporate Baju Kurung traditional identity is solved by categorization of the garments into several different groups according to their style and character. The identity of traditional Baju Kurung is strengthened by imparting the method of evaluation of Malay aesthetic principles to the garment. This will be an added value to the existing character definition of Baju Kurung. Character definition of the traditional Baju Kurung will protect the Baju Kurung from being misused by fashion industries. Based on the development of the Baju Kurung it is believed that Baju Kurung will continue to inspire modem Malay garments in the future. It is hoped that this research will be a major reference in future study in related field.